The Impact of the 1994 Federal Assault Weapons Ban on Gun Markets: An Assessment of Short-Term Primary and Secondary Market Effects - Koper, Christopher S. (Journal of quantitative criminology, 2002)
The reactions of the gun market, including those of producers, wholesalers, retailers, and consumers, play an important role in shaping the potential impact of gun control policies on gun crime. As a case in point, this paper examines the federal Violent Crime Control and Law Enforcement Act of 1994 , which bans a group of military-style semiautomatic firearms (i.e., assault weapons). Using a variety of national and local data sources, we assess the short-term (1994–1996) impact of the assault weapons ban on gun markets, examining trends in prices and production of the banned weapons in legal markets and assessing the availability of the banned weapons in illicit markets as measured by criminal use. Prices of assault weapons rose substantially around the time of the ban's enactment, reducing the availability of assault weapons to criminal users in the very short run. However, a surge in assault weapon production just before the ban caused prices to fall in the months following the ban. Implications of the findings for assessing this and other gun control policies are discussed.